Recombinant Yebf-Cas9 fusion enzyme from thermophilic Geobacillus kaustophilus interaction with sgRNA by in silico method. - Muthi`ah, Hajar; Laksmi, Fina Amreta; Nugraha, Yudhi; Khayrani, Apriliana Cahya; Nurhayati, Retno Wahyu; Mohamad Ali, Mohd Shukuri; Lischer, Kenny (Faculty of Engineering, Universitas Indonesia, 2025)
Genetic engineering is a process that changes the structure of an organism by removing, inserting, or modifying its genetic material. Currently, the most widely used method in genetic engineering is CRISPR-Cas9, representing “Clustered Regularly Interspaced Short Palindromic Repeat-Associated Protein 9“. As an intracellular enzyme, the production of Cas9 is complex and costly due to the need for extraction and purification. In comparison, YebF is a protein that can be localized extracellularly. By fusing YebF with Cas9 (YebF-Cas9), it is possible to express and localize Cas9 extracellularly. This fusion potentially alters Cas9 ability to bind with sgRNA (single guide RNA). Therefore, this study aimed to explore the interaction between sgRNA and Cas9 from Geobacillus kaustophilus fused with YebF using in silico methods. In the in silico experiment, the molecular docking method was used to determine biomolecular interactions with variations in sgRNA, namely spacer 10, 20, 30 nt, repeat 16, 25, 36 nt, and tracrRNA 63, 98, 140 nt. The results showed that changes in the length of the spacer, repeat, and tracrRNA could affect the level of binding affinity formed in YebF-Cas9-sgRNA complex from Geobacillus kaustophilus. The optimal length of the molecular docking results in terms of affinity and position was in the variation of 30 nt spacer with 16 nt repeat and 98 nt tracrRNA, with the binding affinity of -419.24 kcal/mol.